The molecular dynamics simulation of 2,6-dihydroxybenzoic acid crytal in ethanol, methanol and p-xylene at 20°c using compass force field - Nurul Kalyisah, Abd Khar (2012)
2,6-dihydroxybenzoic acid is an active pharmaceutical ingredient which will exhibits polymorphism when it is in crystalline form.Different polymorphs exhibit different physical properties.From previous study found,the selection of appropriate solvent plays a significant role in the formation of the desirable FI and FII polymorph.In this research,molecular dynamics (MD) were applied to simulate the behavior of 2,6-dihydroxybenzoic (DHB) acid crystal in ethanol,methanol and p-xylene at 20oC using COMPASS force field.The objective of this research is to study the effect of various solvents on 2,6-dihydroxybenzoic acid crystal.MD simulation is performed using Material Studio for ethanol, methanol,p-xylene and 2,6-dihydroxybenzoic acid by applying COMPASS Force Field together with Forcite and Amourphous Cell Module.The dynamics run for pure solvent is performed initially in NVE ensemble at 200 ps and followed by NPT ensemble at 800 ps.From the trajectory files,the density, radial distribution function(rdf)and diffusion coefficient were analyzed and calculated.It is expected that MD simulation able to correlate rdf with the specific functional group in solvents structure.Based on the rdf,the probabilities of finding specific intermolecular interactions of hydrogen bond which is a relatively strong form of intermolecular attraction in specific solvents can be assessed.It is a type of attractive intermolecular force that exists between two partial electric charges of opposite polarity.The difference atomic interaction from the rdf trends show that the type of solvent use in 2,6-DHB crystallization process may lead to the polymorphism